Retinol-binding protein 4 is a potential biomarker of changes in lean mass in postmenopausal women - de Queiroz Freitas, Augusto Corrêa (2024)
Identifying biomarkers can help in the early detection of muscle loss and drive the development of new therapies. Research suggests a potential link between retinol-binding protein 4 (RBP4) and muscle mass, particularly in postmenopausal women. This study aimed to examine the association between baseline RBP4 levels and changes in appendicular lean mass (ALM), an indicator of muscle mass, in postmenopausal women. A 12-month follow-up period (n = 153) included baseline and 12-month ALM assessments using DXA. ALM was normalized to squared height (ALMI). Baseline evaluations encompassed insulin resistance via HOMA-IR and immunoassay magnetic bead panel measurements of RPB4, IL-6, TNF-α, and IL-10. Postmenopausal women were categorized into higher (n = 77) and lower (n = 76) RPB4 groups based on baseline RPB4 values. Their changes in ALMI were compared using Mann–Whitney tests. General linear model was employed to evaluate the predictive power of baseline RBP4 for ALMI changes, adjusting for confounding variables: age, physical activity, smoking status, body fat, HOMA-IR, inflammatory markers (TNF-α and IL-6), and anti-inflammatory factor (IL-10). The higher RBP4 group exhibited a more pro-nounced reduction in ALMI compared to the lower RBP4 group (Higher RBP4 = −0.39 kg/m2, 95% CI: −0.48 to −0.31 kg/m2 vs. Lower RBP4 = −0.24 kg/m2, 95% CI: −0.32 to −0.15 kg/m2, P = 0.011). After adjusting for confounding factors, the association between baseline RBP4 changes and ALMI remained (b = −0.008, SE = 0.002, P < 0.001), indicating higher baseline RBP4 values linked to greater ALMI reduction. Our findings support RBP4 as a potential biomarker for changes in muscle mass in postmenopausal women.